A study on the application of an artificial neural algorithm in the color matching of Taiwanese cultural and creative commodities. Issue 4 (10th June 2014) - Hsiao, Shih‐Wen; Wang, Ming‐Feng; Lee, Dai‐Jung; Chen, Chien‐Wei
Abstract In the recent years, great importance has been shown toward the cultural creativity in Taiwan. Cultural identification and determining how best to apply it to commercial products require investigating and compiling a vast amount of cultural information, along with the individual ideas of designers, to develop new cultural products. During the product development and design process, the color scheme is the final and most important element. It not only represents the first image of the product but also elicits the important first‐sight impression of consumers. Consequently, color ranks first in cultural commodity development. By understanding the Taiwanese culture, as well as assessing, verifying, and internalizing it into the materials that can be used by the designers, this study uses an artificial neural network system and simplifies the collected pictures that are representative of the Taiwanese culture into groups of different matching colors to assist designers in developing cultural commodities with different features and according to different cultural styles. © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 341–351, 2015